Supporting Careers of Women in Clinical Immunology: From Conceptualization to Implementation - Dimitriades, Victoria R.; Freeman, Alexandra F.; Henrickson, Sarah E.; Abraham, Roshini S. (Frontiers in Pediatrics, 2022)
Women have proven themselves integral to academic and clinical excellence, diversity, and all aspects of the missions of various Immunology societies. Yet, women in Immunology still face challenges in academia and leadership positions, as many others have noted in medical and research specialties, with resultant attrition from the advancement pipeline. A concerted effort and thoughtful strategies are required to support the careers of women across biomedical science and medicine, to ensure the success of women in all aspects of academic, research and clinical life. While many strategies warrant consideration in this process, the conscious effort to promote gender balance by academic medical and scientific journals and conference organizing committees can help to expand not only the high-quality presentations of valuable work, but may thereby facilitate promotion of women as members of editorial boards, professional committees, and in other invited positions. In early 2017, with the primary goal to support and encourage the promotion of women at all levels of training and career advancement, the Clinical Immunology Society (CIS) launched their Women in Clinical Immunology Sciences (WCIS) committee. This committee included members at various stages of their careers, with the intentional recruitment of all genders. The committee’s purpose was to help current and future members to attain their full academic potential via mentorship, sponsorship, professional development, and leadership, in an inclusive and supportive climate.